Intracellular Photocatalytic NADH/NAD(P)H Oxidation for Cancer Drug Development - Yadav A.K.; Kushwaha R.; Mandal A.A.; Mandal A.; Banerjee S. (My University, 2025)
Photocatalytic cancer therapy (PCT) has emerged as a cutting-edge anticancer mechanism of action, harnessing light energy to mediate the catalytic oxidation of intracellular substrates. PCT is of significant current importance due to its potential to address the limitations of conventional chemotherapy, particularly drug resistance and side effects. This approach offers a noninvasive, targeted cancer treatment option by utilizing metal-based photocatalysts to induce redox and metabolic disorders within cancer cells. The photocatalysts disrupt the cancer cell metabolism by converting NADH/NAD(P)H to NAD+/NAD(P)+ via catalytic photoredox processes, altering intracellular NAD+/NADH or NAD(P)+/NAD(P)H ratios, which are crucial for cellular metabolism. Ir(III), Ru(II), Re(I), and Os(II) photocatalysts demonstrated promising PCT efficacy. Despite these developments, gaps remain in the literature for translating this new anticancer mechanism into clinical trials. This Perspective critically examines the developments in this research area and provides future directions for designing efficient photocatalysts for PCT. © 2025 American Chemical Society.